Diabetes Myonecrosis: A Debilitating Complication in an Indigenous Young Woman With Long Standing Type 1 Diabetes Mellitus - Jinwen He; Liyan Wang; Thomas Robertson; Swetha Rangaswamaiah; Usman H. Malabu (Case Reports in Endocrinology)
A 24-year-old Indigenous Australian female with long-standing, poorly controlled type 1 diabetes mellitus (T1DM) presented with 3 months’ history of unilateral thigh swelling and pain. Her laboratory investigations showed evidence of a persistent inflammatory state with normal creatine kinase. Infectious and autoimmune investigations were negative. Imaging demonstrated evidence of muscular oedema and atrophy. Muscular pain and swelling have a broad list of differential diagnoses. This case highlights a rare but potentially debilitating complication of diabetes mellitus—diabetic myonecrosis with its challenges in reaching a definitive diagnosis due to non-specific symptomology and laboratory findings. However, it is an important differential of leg pain and swelling to consider, particularly in those with long-standing diabetes and pre-existing microvascular complications. Glycaemic control is paramount in preventing this potentially severe diabetic complication.